Institutional and financial support of the development of rural areas - Hazuda, Mykhailo; Makukh, Tamara; Hazuda, Lesya; Voloshchuk, Nadiia (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
In this article, particular aspects of institutional and financial support of development of rural areas have been considered. Law and legislative approaches towards regulation of powers and cooperation of public authorities with local governments and a particular territorial community have been generalized. It has been indicated that regional aspect of formation of institutional and financial component for support of rural areas development is being substantiated by the Concept of steady development of rural areas of Transcarpathian region along with the Transcarpathian Region Development Strategy, which had already been determined until 2027. Beside necessary is security of practical realization of connection of investigation costs, especially state financial support of projects for rural areas’ growth and developing a state system for attracting the unemployed in rural areas and distant mountain sub-regions using up-to-date information technologies are extremely urgent but critical. This idea is extremely urgent in the quarantine caused by COVID-19. Analytical and problem aspect of support for rural areas development on the example of a definite region (Transcarpathia) has been highlighted. The experience of foreign countries in promotion of rural areas’ development has been studied. An emphasis has been placed upon the necessity to distinguish the problems of rural areas’ development, which impede extended notion of investigated areas.